Examining User Intention Toward Cloud-Based Accounting Information System Adoption - Erika Handayani; Zaldy Adrianto; Hamzah Ritchi (Universitas Padjadjaran, 2021)
This research examined the association of users perceived ease of use, usefulness, and risks with the intention of cloud-based accounting information systems (AIS) adoption. The research involved 41 small-medium enterprises (SMEs) in Bandung as the samples of the study. The data was collected using a questionnaires instrument with a purposive sampling technique. The results showed that perceived ease of use (PEOU) and usefulness (PU) was positively associated with adopting a cloud-based accounting information system. Meanwhile, the perceived risk (PR) had no significant influence on the cloud-based accounting information system’s perceived usefulness (PU). However, the perceived risk significantly influenced to intention to use (IU) cloud-based accounting information system.